EVALUATE OF THE TREATMENT OUTCOMES OF ORONASAL FISTULA CLOSURE USING MUCOPERIOSTEAL FLAP IN PATIENTS WITH CLEFT LIP AND PALATE AT THE HANOI CENTRAL ODONTO-STOMATOLOGY HOSPITAL FROM JUNE 2019 TO SEPTEMBER 2020 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment outcomes of the oronasal fistula using mucoperiosteal flaps in patients with cleft lip and palate at the Hanoi Central Odonto-Stomatology Hospital from June 2019 to September 2020. Subjects and Methods: Clinical intervention study without control group.Results: The average age was 13.88 ± 4.93; the youngest was 2 years old and the oldest was 26 years old; the majority were over 12 years old, accounting for 60.6%. In the first week, the surgical wound condition was generally good, with swelling occurring in most cases (90.9%). 100% of patients did not experience complications such as bleeding, infection, or wound dehiscence. Three months after surgery, only 1 out of 33 patients experienced recurrence of the fistula and required re-surgery. After six months, most patients had good treatment outcomes, with only 6.1% requiring further re-surgery using a different method. 93.9% of patients experienced relief from reflux during eating, were satisfied, and had improved quality of life. Conclusion: In the group of small stomata (< 5mm) selected for the study, closure of the stomata resolved the problem of reflux from the mouth to the nose during eating and drinking; in most cases, there was no improvement in speech
Keywords: oronasal fistula, cleft lip and palate.